2018
DOI: 10.1186/s13048-018-0400-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potentials of Quercetin in management of polycystic ovarian syndrome using Letrozole induced rat model: a histological and a biochemical study

Abstract: BackgroundPCOS is a leading endocrinopathy of young women instigating androgens elevation, insulin resistance, obesity, cardiometabolic and menstrual complications. The study investigated the effects of quercetin in a letrozole induced rat model of polycystic ovarian syndrome, which displayed both clinical and metabolic features as in PCOS women.MethodsFemale Sprague Dawley (SD) rats were divided into four groups; control group received aqueous solution of carboxymethyl (CMC 0.5%); PCOS group administered with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 57 publications
(66 reference statements)
10
72
0
Order By: Relevance
“…However, there was a significant troxerutin-caused (300 mg/kg) decline in hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5~3 mIU/ml [34,35], FSH levels varied from 8mIU/ml to 20mIU/ml [26,36] and testosterone varied from 0.2 to 10 ng/ml [34,[36][37][38][39], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was a significant troxerutin-caused (300 mg/kg) decline in hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5~3 mIU/ml [34,35], FSH levels varied from 8mIU/ml to 20mIU/ml [26,36] and testosterone varied from 0.2 to 10 ng/ml [34,[36][37][38][39], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Discussionsupporting
confidence: 92%
“…However, there was a significant troxerutin-caused ( 300 mg/kg) decline in serum and hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5 ~ 3 mIU/ml [32,33], FSH levels varied from 8mIU/ml to 20mIU/ml [22,34]and testosterone varied from 0.2 to 10 ng/ml [32,[34][35][36][37], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Possession Of Beneficial Effects On Animal Models Of Differesupporting
confidence: 92%
“…SFN mediated antioxidant effects may have occurred through activation of the transcription factor; nuclear factor-erythroid 2-related factor 2 (Nrf2), which increases gene expression of endogenous antioxidant proteins such as SOD [85,86]. Moreover, quercetin, a flavonoid present in broccoli, was proved to have the potentials to alleviate the hormonal and metabolic disturbances occurring in PCOS [87].…”
Section: Discussionmentioning
confidence: 99%